Extracellular HIV-1 Tat Mediates Increased Glutamate in the CNS Leading to Onset of Senescence and Progression of HAND - Marino, Jamie; Wigdahl, Brian; Nonnemacher, Michael R. (Frontiers in Aging Neuroscience, 2020)
Human immunodeficiency virus type 1 (HIV-1)- associated neurocognitive disorders (HAND) is a disease of neurologic impairment that involves mechanisms of damage similar to other degenerative neurologic diseases such as Alzheimer’s disease (AD). In the current era of antiretroviral therapy (ART), HIV-1 replication is well-suppressed, and yet, HIV-1-infected patients still have high levels of chronic inflammation, indicating that factors other than viral replication are contributing to the development of neurocognitive impairment in these patients. The underlying mechanisms of HAND are still unknown, but the HIV-1 protein, Tat, has been highlighted as a potential viral product that contributes to the development of cognitive impairment. In AD, the presence of senescent cells in the CNS has been discussed as a contributing factor to the progression of cognitive decline and may be a mechanism also involved in the development of HAND. This mini-review discusses the viral protein HIV-1 Tat, and its potential to induce senescence in the CNS, contributing to the development of HAND.